Indonesia di Usia 80 Tahun: Refleksi Kritis Kebangsaan - Palindangan, Linus Kali; Manurung, Antonius Dieben Robinson; Ajis, Ahmad (Indonesian Character Journal, 2026)
In 2025, the Republic of Indonesia marks its 80th anniversary, offering a critical moment to evaluate the nation’s collective performance across key sectors. This study provides a comprehensive and reflective assessment of Indonesia’s political, economic, social, educational, cultural, environmental, and global development trajectories. Using a qualitative-descriptive approach and a systematic literature review, the analysis draws on official government documents, international institutional reports, scholarly publications, and credible media investigations. The findings show that although Indonesia has made notable progress—emerging as the world’s third-largest democracy and Southeast Asia’s largest economy—substantial structural challenges remain. Democratic consolidation is hindered by ethical violations in judicial institutions, increasing oligarchic influence, and stagnation in anti-corruption efforts. Economic growth has not fully translated into equitable distribution, evidenced by persistent inequality, governance failures in social assistance, and continued labor-market mismatches. The education and health sectors demonstrate improved access yet uneven quality, while environmental degradation and a slow clean-energy transition pose urgent threats to sustainability. Globally, Indonesia plays an active diplomatic role, but institutional constraints limit its international effectiveness and innovation capacity. The study aims at arguing that Indonesia’s 80-year milestone should serve as a catalyst for reaffirming constitutional ideals and strengthening governance, equity, and sustainability as essential foundations for realizing the vision of 2045 Golden Indonesia.